Distal Oblique Bundle Reconstruction and Distal Radioulnar Joint Instability - Riggenbach, Michael D.; Conrad, Bryan P.; Wright, Thomas W.; Dell, Paul C. (Journal of Wrist Surgery, 2013)
Background This study created an anatomic reconstruction of the distal oblique bundle (DOB) of the interosseous membrane to determine its effect on distal radioulnar joint (DRUJ) instability and compare this technique with distal radioulnar ligament (DRUL) reconstruction.Questions/Purposes We hypothesized that this reconstruction would provide equivalent stability to DRUL reconstruction and that combining the two techniques would enhance stability.Methods Six cadaveric upper limbs were affixed to a custom frame. The volar/dorsal translation of the radius relative to the ulna was measured in 60° pronation, neutral, and 60° supination. Translation was sequentially measured with the DRUJ intact, with sectioned DRULs and triangular fibrocartilaginous complex (TFCC), and with sectioned DOBs. Reconstructions were performed on the DRULs, on the DOB tensioned in both neutral and supination, and employing both techniques.Results The DOB reconstruction, tensioned both in the neutral position and in 60° supination, was more stable than the partial and complete instability in 6/6 specimens in pronation and the neutral position and in 5/6 specimens in supination. The DOB reconstruction and the DOB reconstruction tensioned in supination were more stable than the DRUL reconstruction in 4/6 patients. Combining the two techniques did not further reduce translation.Conclusions The DOB reconstruction is capable of improving stability in the unstable DRUJ.
Keywords: distal oblique bundle; distal radioulnar joint; stability; wrist